A kommentekért való felelősség bírói gyakorlatának evolúciója - Pádár, Henrietta (Debreceni Jogi Műhely, 2018)
The article focuses on the examination of the judicial practice related to the liability for reader’s comments. Comments have become an important instrument for internet communication and expression, however they also cause specific legal problems. Internet Content Providers (ICP) have offered such content so far, disclosure of which was the result of editorial’s decision, but now they play a role in the disclosure of such contents, that they do not have direct contact with. The examination of liability for comments is further complicated by the features of the online environment, because the courts shall have to overcome the problems of the scheme of special definitions. Courts have failed as yet to provide a satisfactory solution for the problem: who shall remain liable for the infringements appearing in anonymous reader’s contents? Therefore the article is an attempt to present the development of the judicial practice from the beginning to the current opinion appearing these days.